2003
DOI: 10.1119/1.1607337
|View full text |Cite
|
Sign up to set email alerts
|

Helping students develop an understanding of Archimedes’ principle. II. Development of research-based instructional materials

Abstract: This paper is the second of two that describe how research on student understanding of Archimedes’ principle is being used to guide the development of instructional materials to supplement instruction on this topic in typical introductory courses. The instructional materials that resulted have proven to be effective. Also discussed are instructional materials for special courses and workshops for K–8 teachers. Evidence is presented that, on some tasks, teachers who have worked through these materials perform m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 5 publications
4
25
0
11
Order By: Relevance
“…Hake found that students in the latter courses averaged gains that were twice as large as those in the traditional classes (Hake, 1998(Hake, , 2002. Results consistent with these have since been obtained by numerous other physics research groups (Ambrose et al, 1999;Redish, 2003;Heron et al, 2003;Loverude et al, 2003). Interactive engagement of students in their own learning measurably enhanced the conceptual development and problem-solving abilities of the learners.…”
Section: Classroom Studiessupporting
confidence: 71%
“…Hake found that students in the latter courses averaged gains that were twice as large as those in the traditional classes (Hake, 1998(Hake, , 2002. Results consistent with these have since been obtained by numerous other physics research groups (Ambrose et al, 1999;Redish, 2003;Heron et al, 2003;Loverude et al, 2003). Interactive engagement of students in their own learning measurably enhanced the conceptual development and problem-solving abilities of the learners.…”
Section: Classroom Studiessupporting
confidence: 71%
“…A series of studies by the University of Washington Physics Education Group focused on student understanding of static fluids and related topics: the ideal gas law [26,27] and volume of an ideal gas [28], buoyancy [2,3,29], and hydrostatic pressure [4]. While buoyancy was not directly applicable to our work, the ideal gas studies informed our perspective on microscopic versus macroscopic approaches (detailed in the next section), and tutorial development (Sec.…”
Section: A Pressure and Static Fluidsmentioning
confidence: 99%
“…The misconceptions perspective is a framework used in designing activities, and focuses on carefully delineating student misconceptions and difficulties and employing elicit-confront-resolve strategies in the development of the interventions; curricula are assessed using pre-and postconceptual tests [2][3][4]. One concern with this approach is that the elicit-confront-resolve approach sends the undesirable epistemological message that students' everyday experiences are not valuable in the physics classroom [5] (p. 633).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of buoyancy is a prerequisite for learning about Archimedes' principle, and Heron et al (2003) found that it was helpful to provide learners with laboratory experience in buoyancy prior to introducing Archimedes' principle, in order to address intuitive ideas and misconceptions. The learners who participated in our study had already been taught about buoyancy by their teacher in regular classes before they participated in our study, but to ensure that all of them understood buoyancy and to familiarize them with the structure of the learning environment, including the laboratory and the EDT, we chose to present a set of inquiries about buoyancy prior to introducing Archimedes' principle.…”
Section: Domain: Archimedes' Principlementioning
confidence: 99%
“…The domain involved in the present study was Archimedes' principle, which states that ''an object fully or partially immersed in a fluid is buoyed up by a force equal to the weight of the fluid that the object displaces'' (Halliday et al 1997, as cited in Hughes 2005. This principle therefore entails that the mass of fluid displaced by a floating or suspended object is equal to the mass of the object, and the volume of fluid displaced by a sunken or suspended object is equal to the volume of the object (Hughes 2005).…”
Section: Domain: Archimedes' Principlementioning
confidence: 99%